Haematology : from the image to the diagnosis - Leach, Richard M. 4 (Haematologist),0 16; Bain, Barbara J.; 5 (Hoboken, NJ : Wiley-Blackwell, 2022)
Despite the tremendous advances that have occurred in diagnostic haematopathology in recent decades haematology remains firmly based on a clinical assessment of the patient, on basic laboratory tests and on a critical assessment of peripheral blood and bone marrow films. In this book we seek to show how an appreciation of blood and bone marrow morphology, assessed with knowledge of the clinical context, can lead to a provisional or, sometimes, a definitive diagnosis that guides further investigation and management. Each of the 101 themes is followed by a related multiple choice question with the preferred answers and further discussion being found in the second part of the book. The themes are sometimes single cases and sometimes a composite of related cases. The book is directed at consultants and trainees in haematology and haematopathology and at clinical and biomedical scientists in these disciplines. We hope that readers will share our enjoyment of the constant sense of discovery that accompanies haematological morphology. All magnifications are stated in terms of the objective used. Common abbreviations that may be used without definition are given on pages xy. Other abbreviations are defined on first use in a theme. All images are of films stained with a May-Grünwald-Giemsa stain unless stated otherwise. The cases are not arranged thematically, since a more random arrangement better approximates to real life. We wish to thank our clinical and laboratory colleagues with whom we have collaborated over many years--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; diagnosis -- Hematologic Diseases;Blood Physiological Phenomena -- 20; 20; Examination Questions;Case Reports -- 2